Epistolary writing and the teaching of languages: the practical manuals of commercial correspondence by G. B. Melzi (1878) - M.ª García Aranda, Ángeles (Romanica Olomucensia, 2019)
The increase in commercial transactions during the 19th century led to an important growth in the publication of commercial teaching materials in the form of what were known as correspondence arts or manuals. This paper deals with the ones that were written, and adapted to four languages, with the title Practical Handbook of Commercial Correspondence, by Giovanni Battista Melzi, who, following the classics, considers that letters are written conversations and, therefore, the best way to learn a foreign language. In these pages a detailed analysis of Melzi's manual, adapted to French, English, Italian, German, and Spanish (1878), is presented and the contents of the letters and their typology are reviewed, together with the clarifications and explanations included as footnotes by the author. Letters and footnotes become a valid resource for learning a second language, since they include very interesting observations about treatment formulae, the forms and uses of pronouns and verbs, conjunctions, interjections, adverbs, prepositions, proper names, punctuation, the lexicon, or spelling and phonetics. The content of these manuals responds to linguistic and commercial interests, so that the letters and lexicon, despite having been widely used in the history of language teaching, are, according to its author, the best way to learn Spanish, French, English, German, or Italian at the end of the century.
Keywords: commercial Spanish; correspondence; teaching of language; 19th century; Giovanni Battista Melzi